'We're here tae mak a difference' - The Group; Jeremy Millar (Scottish Journal of Residential Child Care)
This paper presents an account of the work undertaken by The Group. The Group comprises a number of young people who represent the voice of those with care experiences. They have been involved in the education of social work students within the School of Applied Social Studies at the Robert Gordon University (RGU) for the past two years. Writing the paper presented a challenge in terms of how the views of the participants could be presented for an academic journal. The Group members are all articulate and confident at sharing their views verbally, but many feel let down by the education system and are less confident in their writing skills. After some thought and discussion it was decided that group members would give their input by way of a digital recording device modelled on a 'Big Brother-style' diary room.